Artifact. Art-Object. Argument. An Object in Fine Arts: Objectives, Methods, Results - Jijina, Nadia C.; Maltseva, Svetlana V.; Staniukovich-Denisova, Ekaterina Iu. (Actual Problems of Theory and History of Art, 2017)
This article presents the volume of collected papers that were delivered as reports at the “Actual Problems of History and Theory of Art VII” International Conference held in Saint Petersburg in October, 2016.The book mainly contains the materials on the art from ancient times till the Renaissance and art critical surveys. It deals with the actual theoretical problems of the history of fine arts, and Oriental studies, as well as the interlacement of religion and artistic culture.Taking the main debating topic and the emphasis of the conference of 2016 into consideration, along with the idea of an art-object that was in the focus of the conference, book is also focused on the problems of insightand interpretation of artistic objects from the moment of creation to the time of their actual gaining, when they can be seen by viewers.